The Role and Effectiveness of Judges in Reducing Divorce Rate (Case Study in the Religious Court of Tegal District) - Haikal, M. Surya (Proceedings Series on Social Sciences & Humanities, 2024)
A harmonious and happy marriage is the main goal of marriage. However, in reality, divorce is increasingly common in Indonesia. The Central Statistics Agency (BPS) shows an increase in the divorce rate in recent years. This is a concern for many parties. Lack of communication and understanding between partners is one of the main factors. This research aims to understand the role of judges in helping couples resolve conflicts and reach agreements in the divorce process. Apart from that, this research also examines strategies to increase community access to mediation and counseling services in the divorce process. The research method used is empirical legal research with a socio-legal approach. This research analyzes the law and its practices in society. It is hoped that the research results will provide a deeper understanding of the role of judges in helping to resolve conflicts and reach agreements in the divorce process. It is also hoped that the research findings can provide input for increasing public access to mediation and counseling services in the divorce process.